IN THE DIMENSIONS OF ETERNITY: IVAN KOTLIAREVSKYI’S "ENEIDA" ("AENEID") AS ONE OF THE MOST SIGNIFICANT EXAMPLES OF WORLD BURLESQUE LITERATURE - Maftyn, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The aim of the article is to actualize I. Kotliarevskyi’s "Eneida" in the modern literary space, to analyze the ambivalence of the assessment of the poem in the literary-critical thought of past centuries and the present, to find out the reasons for the Ukrainian artist’s appeal to the poem of the ancient author, to reveal the genetic kinship of the artist’s work with Ukrainian folklore (in particular, with folk laughter culture), with the "school subculture" and its protest nature, to find out the importance of the work for the receptive horizons of the modern Ukrainian. To achieve the goal set, the methodology of hermeneutics, cultural-historical and culturological methods were used. Results. A review of literary-critical and literary studies, a reading of the work from the perspective of modernity makes it possible to reveal the nuances hidden in the palimpsest nature of Kotliarevskyi’s writing, which are important for our present, in particular the threat of the transformation of the "bui-tur" (bos urus) into the "ox in the yoke", which appears on the pages of the work as a clear warning. The article emphasizes the creative continuation of the old burlesque tradition by the Ukrainian author, while the experience of European literary predecessors in combination with the folk laughing tradition and the influences of the grassroots baroque gave a new quality to the work, which makes the poem by I. Kotliarevskyi one of the most prominent examples of the world burlesque tradition and at the same time – a qualitatively different work, alive and relevant in our time. In I. Kotliarevskyi’s "Eneida", not only intertextual "patterns" are palimpsestically visible: a deep subtextual layer that is projected onto Ukrainian existence in three dimensions - past, present, future - and makes this work qualitatively different from all previously known reworkings of Virgil’s poem. The scientific novelty of the article lies in the modern reading of I. Kotliarevskyi’s work, taking into account the opinions of literary scholars of both the previous era and the authors of the latest research.